Effects of Exercise During Pregnancy on Mode of Delivery: A Meta-Analysis - Garcia-Hermoso, A (Taylor and Francis Ltd, 2015)
Introduction. We conducted a systematic review and meta-analysis to examine the influence of physical exercise interventions on the mode of delivery of healthy pregnant women with low to moderate levels of physical activity. Material and Methods. Key words were used to conduct a computerized search for articles on the topic in six databases: Cochrane Library Plus, Science Direct, EMBASE, PubMed, Web of Science and ClinicalTrials.gov. Ten randomized controlled trials were identified and included in the meta-analysis. Main outcome measures were mode of delivery (normal, instrumental vaginal, or cesarean delivery) and physical activity. Results. Relative risk reductions and their 95% confidence interval were calculated for each study, and the heterogeneity of the studies was estimated using Cochran s Q statistic. The evidence suggests that physical exercise during pregnancy may increase the likelihood of normal delivery (relative risk = 1.12, 95% confidence interval 1.01-1.24; p = 0.041), in particular when exercise takes place during the second and third trimesters (relative risk = 1.14, 95% confidence interval 1.01-1.32; p = 0.048), even reducing the risk of cesarean delivery (relative risk = 0.66, 95% confidence interval 0.46-0.96; p = 0.028). Conclusions. Regular exercise during pregnancy appears to modestly increase the chance for normal delivery among healthy pregnant women. This applies to women with low to moderate levels of physical activity, but studies are needed to understand better the effect of physical exercise of moderate to vigorous intensity in the different trimesters. © 2015 Nordic Federation of Societies of Obstetrics and Gynecology.